1977
DOI: 10.1017/s0305000900001641
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of before and after in logical and arbitrary sequences

Abstract: Pre-school children were required to act out a series of two-event sequences conjoined by either before or after. The sentences to be acted out consisted of either a meaningfully or an arbitrarily ordered sequence of events. Performance was markedly superior for meaningfully ordered sequences. It is suggested that the meanings of before and after must be acquired in situations which provide contextual support, and only then can be applied in situations which do not provide such support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
1
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 6 publications
8
45
1
1
Order By: Relevance
“…, the taking off of the hat happens after the taking off of the coat but is mentioned first. A number of studies have suggested that three-to four-year-olds tend to use an order-of-mention strategy to understand sentences involving 'before' and 'after' , meaning that they will typically have difficulty with sentences in which order of mention does not match event order (Blything et al, 2015;French & Brown, 1977;McCormack & Hanley, 2011;Trosborg, 1982). One possibility is that children's ability to understand such non-chronological sentences is primarily constrained by their working memory skills (Blything et al, 2015), because of the need to mentally manipulate the sentence content.…”
Section: Stage (C): Linear Event-independent Time (4-5 Years)mentioning
confidence: 99%
“…, the taking off of the hat happens after the taking off of the coat but is mentioned first. A number of studies have suggested that three-to four-year-olds tend to use an order-of-mention strategy to understand sentences involving 'before' and 'after' , meaning that they will typically have difficulty with sentences in which order of mention does not match event order (Blything et al, 2015;French & Brown, 1977;McCormack & Hanley, 2011;Trosborg, 1982). One possibility is that children's ability to understand such non-chronological sentences is primarily constrained by their working memory skills (Blything et al, 2015), because of the need to mentally manipulate the sentence content.…”
Section: Stage (C): Linear Event-independent Time (4-5 Years)mentioning
confidence: 99%
“…But some sentences connected by means of the temporal conjunctions are easier than others, in that the sequential order between the two events/states might be arbitrary as in (9) Before Soren cleaned his boots, he polished his shoes, (Before 2) (10) Mette drank the milk, after she ate the cake, (After 2) or there is a logical order of sequences, as in (11) Before Mette went out, she put on her coat (Before 2) (12) Soren went to bed, after he brushed his teeth (After 2) in which sentences the reversed order would be odd. In sentences in which the order of the two clauses has to be reversed to correspond to event order, comprehension is greatly facilitated if there is a logical connection between the two clauses (French & Brown 1977, Kavanaugh 1979, Trosborg 1980.…”
Section: Discussionmentioning
confidence: 99%
“…Clark 1970, Ferreiro & Sinclair 1971, Coker & Legum 1975, French & Brown 1977. Children tend to rely on an order of mention strategy interpreting the sentence as if what is mentioned first is also what happens first.…”
Section: Temporally Related Sentencesmentioning
confidence: 99%
“…It was clear from our informal observations of subordinators that the semantic content of what was talked about (temporal or causal) had a much stronger impact on adverbial clause placement than the child's age. Previous findings indicate that young children have a better understanding of temporal adverbial clauses (using connectives such as before and after) in which the order of mention is the same as the order of events (Clark, 1971;French & Brown, 1977;Trosborg, 1982). However, recent findings by Blything and colleagues (2015) using an animation task indicate that while the order of mention effect was evident for the connective before it was not evident for sentences containing after.…”
Section: Clause Typesmentioning
confidence: 96%
“…In addition, in relation to adverbial clauses research shows that young children have greater difficulty, processing those in which the order of presentation is different from the order in which the events occurred (Clark, 1971;French & Brown, 1977;Trosborg, 1982). For these reasons, we might anticipate that we will see some variability in the age at which particular clause constructions are observed in narrative samples.…”
Section: Measures Of Syntactic Complexitymentioning
confidence: 99%